Classroom Management Challenges and Adaptive Strategies of EFL Student Teachers during Teaching Practicum - Qarimah, Siti; Sabarun; Ali Mirza , Akhmad (EDULANGUE, 2025)
Classroom management is a critical component of effective teaching, particularly for English Education student teachers who must navigate the intersection of pedagogical theory and practice in culturally and religiously influenced settings. However, student teachers often face significant challenges, such as student disengagement, language barriers, and undermined authority, which are exacerbated in unique institutional contexts like Indonesia’s Islamic universities. This study explores the classroom management difficulties encountered by 10 student teachers from UIN Palangka Raya during their practicum in Kementerian Agama-affiliated schools, as well as the strategies they employ to address these challenges. Using a qualitative case study approach, data were collected through semi-structured interviews and teaching practicum reports, followed by thematic analysis. Findings revealed that student teachers struggled with low motivation for English learning, passive participation, and cultural-linguistic preferences, compounded by institutional policies that diminished their authority. To mitigate these issues, they adopted strategies such as differentiated instruction, behavioral management techniques, engagement boosters (e.g., gamification), and relationship-building. However, the effectiveness of these strategies was often limited by large class sizes and short practicum durations. The study underscores the need for teacher education programs to incorporate culturally responsive pedagogy, extended practicums, and structured mentorship to better prepare student teachers for the complexities of classroom management in diverse educational settings. These findings highlight the importance of context-specific training to enhance both teacher preparedness and student learning outcomes.